Links of computed tomography sizes lumbar spine in the median-sagittal sections with anthropo-somatotypological parameters of healthy young boy’s mesomorph and endo-mesomorph girls - Pinchuk, S. V.; Gunas, I. V. (Journal of Education, Health and Sport, 2015)
Pinchuk S. V., Gunas I. V. Зв’язки комп’ютерно-томографічних розмірів поперекового відділу хребта на медіанно-сагітальних зрізах з антропо-соматотипологічними параметрами здорових юнаків мезоморфів та дівчат ендо-мезоморфів = Links of computed tomography sizes lumbar spine in the median-sagittal sections with anthropo-somatotypological parameters of healthy young boy’s mesomorph and endo-mesomorph girls. Journal of Education, Health and Sport. 2015;5(8):177-186. ISSN 2391-8306. DOI 10.5281/zenodo.28060 http://dx.doi.org/10.5281/zenodo.28060 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A177-186 https://pbn.nauka.gov.pl/works/607694 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. УДК 611.9:575.191:612.017.1:612:656 ЗВ’ЯЗКИ комп’ютерно-томографічних розмірів поперекового відділу хребта на медіанно-сагітальних зрізах з антропо-соматотипологічними параметрами здорових юнаків МЕЗОМОРФІВ та дівчат ЕНДО-мезоморфів LINKS OF COMPUTED TOMOGRAPHY SIZES LUMBAR SPINE IN THE MEDIAN-SAGITTAL SECTIONS WITH ANTHROPO-SOMATOTYPOLOGICAL PARAMETERS OF HEALTHY YOUNG BOY’S MESOMORPH AND ENDO-MESOMORPH GIRLS С. В. Пінчук, * І. В. Гунас S. V. Pinchuk, I. V. Gunas Вінницький національний медичний університет імені М. І. Пирогова, м. Вінниця; *Міжнародна академія інтегративної антропології, м. Вінниця Vinnitsa N. I. Pirogov National Medical University, Vinnitsa; *International Academy of Integrative Anthropology, Vinnitsa Summary This article describes the features links of computed tomography sizes lumbar spine in the median-sagittal sections with anthropo-somatotypological parameters of healthy young boy’s mesomorph and endo-mesomorph girls and conducted comparing them with the representatives of the general group. In contrast to the general group of girls, in girls endo-mesomorph number of reliable connections to three times reduced, but their power is growing and in young mesomorph, compared with the total group of young men, the number of reliable connections virtually unchanged, but their strength also increases. In girls endo-mesomorph the largest number of reliable connections set with height bodies of the lumbar vertebrae (of which almost half - connections with highly genetically determined anthropometric indicators) and the average width of the bodies of the lumbar vertebrae (of which only 22.2% have relationships with highly genetically determined anthropometric indicators); and in young men mesomorph - height bodies of the lumbar vertebrae (of which only 29.2% have connection with a high genetically determined anthropometric indicators) and height of intervertebral discs (of which 45.0% - connection with a high genetically determined anthropometric indicators). Key words: computed tomography, lumbar spine, morphometry, healthy young women and men, somatotype, correlation. Резюме В статті описані особливості зв’язків комп’ютерно-томографічних розмірів поперекового відділу хребта на медіанно-сагітальних зрізах з антропо-соматотипологічними параметрами у здорових юнаків мезоморфів і дівчат ендо-мезоморфів та проведено їх порівняння із представниками загальних груп. На відміну від дівчат загальної групи, у дівчат ендо-мезоморфів кількість достовірних зв’язків в три рази зменшується, однак їх сила зростає, а в юнаків мезоморфів, порівняно з загальною групою юнаків, кількість достовірних зв’язків практично не змінюється, однак їх сила також зростає. У дівчат ендо-мезоморфів найбільша кількість достовірних зв’язків встановлена з висотою тіл поперекових хребців (з яких майже половина – зв’язки з високо генетично детермінованими антропометричними показниками) та середньою шириною тіл поперекових хребців (з яких лише 22,2 % припадає на зв’язки з високо генетично детермінованими антропометричними показниками); а в юнаків мезоморфів – з висотою тіл поперекових хребців (з яких лише 29,2 % припадає на зв’язки з високо генетично детермінованими антропометричними показниками) та висотою міжхребцевих дисків (з яких 45,0 % – зв’язки з високо генетично детермінованими антропометричними показниками). Ключові слова: комп’ютерна томографія, поперековий відділ хребта, морфометрія, здорові дівчата і юнаки, соматотип, кореляції. Резюме СВЯЗИ КОМПЬЮТЕРНО-ТОМОГРАФИЧЕСКИХ РАЗМЕРОВ поясничного отдела позвоночника НА медианно-сагиттального срезаХ с антропо- соматотипологическиМИ ПАРАМЕТРАМИ ЗДОРОВЫХ ЮНОШЕЙ мезоморфов И ДЕВУШЕК Эндо-мезоморфов. В статье описаны особенности связей компьютерно-томографических размеров поясничного отдела позвоночника на медианно-сагиттальных срезах с антропо-соматотипологическими параметрами у здоровых юношей мезоморфов и девушек эндо-мезоморфов и проведено их сравнение с представителями общих групп. В отличие от девочек общей группы, у девочек эндо-мезоморфов колличество достоверных связей в три раза уменьшается, однако их сила возрастает, а у юношей мезоморфов, в сравнении с общей группой юношей, колличество достоверных связей практически не изменяется, однако их сила также возрастает. У девушек эндо-мезоморфов наибольшее колличество достоверных связей установлено с высотой тел поясничных позвонков (из которых почти половина – связи с высоко генетически детерминированными антропометрическими показателями) и средней шириной тел поясничных позвонков (из которых лишь 22,2 % приходится на связи с высоко генетически детерминированными антропометрическими показателями); а у юношей мезоморфов – с высотой тел поясничных позвонков (из которых лишь 29,2 % приходится на связи с высоко генетически детерминированными антропометрическими показателями) и висотой межпозвоночных дисков (из которых 45,0 % – связи с высоко генетически детерминированными антропометрическими показателями). Ключевые слова: компьютерная томография, поясничный отдел позвоночника, морфометрия, здоровые девушки и юноши, соматотип, корреляции.